A polarizable coarse-grained model for metal, metal oxide and composite metal/metal oxide nanoparticles: development and implementation. Issue 45 (11th November 2022) - Rinkevicius, Zilvinas; Kaminskas, Marius; Palevičius, Paulius; Ragulskis, Minvydas; Bočkutė, Kristina; Sriubas, Mantas; Laukaitis, Giedrius
Abstract : We present a polarizable coarse-grained model for metal, metal oxide, and composite metal/metal oxide nanoparticles with well-defined crystalline surfaces. Abstract : We present a polarizable coarse-grained model for metal, metal oxide, and composite metal/metal oxide nanoparticles with well-defined crystalline surfaces. The developed model uses a low-resolution polarizable "surface beads" representation of the nanoparticle's geometry and pairwise cross nanoparticle potential consisting of van der Waals and electrostatic interaction terms. The electrostatic interaction term of the cross nanoparticle potential incorporates a crucial physical aspect of electrostatic interaction into the metal and metal oxide systems, such as induced surface charges, making it possible to explore the nanoparticles' behavior in complex environments as well as investigate the interplay between electrostatic and van der Waals interactions in nanoparticle systems. The iterative stability, computational scaling, and performance of the presented model was tested on selected systems of gold, titanium dioxide, and composite gold/titanium dioxide nanoparticle systems. The model exhibits robust iterative stability and is able to converge the charge equilibration equation for fluctuating induced charges and dipoles within 10–60 "tug-tow" iterations in challenging situations, like crowded nanoparticle systems or nanoparticle systems in extreme external electric fields. The computation scaling of the presented model is semi-linear with respect to the number of nanoparticles in the system. It slightly varies depending on the size distribution of nanoparticles in a specific nanoparticle system. The computation cost of the model is significantly lower than that of conventional atomistic polarizable force field models and enables the treatment of large nanoparticle systems that are beyond the reach of currently existing atomistic force field models.